The splendor of longing in the Tale of Genji - Field, Norma, 1947- (Princeton, New Jersey : Princeton University Press, 1987)
"Foremost among Japanese literary classics and one of the world's earliest novels, the Tale of Genji was written around the year A.D. 1000 by Murasaki Shikibu, a woman from a declining aristocratic family. For sophistication and insight, Western prose fiction was to wait centuries to rival her work. Norma Field explores the shifting configurations of the Tale, showing how the hero Genji is made and unmade by a series of heroines. Professor Field draws on the riches of both Japanese and Western Scholarship, as well as on her own sensitive reading of the Tale. Included are discussions of the social, psychological, and political dimensions of the aesthetics of this novel, with emphasis on the crucial relationship of erotic and political concerns to prose fictions."--Publisher's description
Three heroines and the making of the hero : dichotomies and substitution: Fujitsubo ; Transgression, exile, and the development of fiction ; The Rokujō lady: pride and possession ; The elusive self in Heian Japan ; Meeting in exile ; At the capital: the Akashi lady as urban aristocrat -- A minor heroine and the unmaking of the hero : Minor chapters and minor heroines ; The noble exile and the stepdaughter ; The eastern pavilion and the battle of the seasons ; The Rokujōin ; Fiction and courtship ; Varieties of carnation: The lady of Ōmi and Tamakazura ; Autumn in Rokujōin ; Tamakazura: the stolen prize -- A substitute for all seasons : The naming of a heroine ; Childhood as a symbolic state ; Idealized banality and its rupture ; The growth of vision ; The staging of death ; The hero alone -- Women beyond the capital : Uji before the Uji chapters ; Secrets, fragrances, and vocation: the men of Uji ; Sisterhood in Uji: Ōigimi, the firstborn ; Between authenticity and substitution: Nakanokimi ; Drifting beyond substitution: Ukifune -- Postscript -- Appendix: chapter titles in the tale of Genji.
Includes bibliographical references (pages 349-361) and index.
Online resource; title from digital title page (viewed on April 2, 2020).
JSTOR
Keywords: Murasaki Shikibu, -- 978?-; Murasaki Shikibu, -- né 978?; Genji monogatari (Murasaki Shikibu); Murasaki Shikibu -- 978-1016; Murasaki Shikibu; Japanese literature -- Heian period, 794-1185 -- History and criticism; Littérature japonaise -- 794-1185 (Époque de Heian) -- Histoire et critique; LITERARY CRITICISM -- Asian -- General; Japanese literature -- Heian period; 794-1185; Criticism, interpretation, etc